The Role of Sufis in The Establishment of The Ottoman Empire - Syed Tahir Abbas (International Journal of Integrated Science and Technology, 2023)
Allah Almighty has sent more or less one hundred and twenty four thousand Prophets to guide mankind, the first lamp of which is Hazrat Adam, peace and blessings be upon him, and the last lamp is Hazrat Rahmatul Alameen. Allah, the Exalted, bestowed countless honors, exaltations and blessings on the Prophet, one of which was the Prophethood and the obedience of the religion of Islam. To describe the introduction of Ottoman Empire and its beginning and development. To describe the introduction of famous Ottoman personalities and Sufis. To describe the role of Sufis in the establishment of the Ottoman Empire.